1978
DOI: 10.1136/jech.32.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Health service 'input' and mortality 'output' in developed countries.

Abstract: SUMMARYThe relationship between age-specific mortality rates and some indices of health facilities and some environmental and dietary factors has been studied in 18 developed countries. The indices of health care are not negatively associated with mortality, and there is a marked positive association between the prevalence of doctors and mortality in the younger age groups. No explanation of this doctor anomaly has so far been found. Gross national product per head is the principal variable which shows a consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
3

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 5 publications
6
109
1
3
Order By: Relevance
“…Nevertheless, it is quite possible that the work of the health care system is more closely related to disability than to mortality, as evidenced by the difficulty experienced in establishing a satisfactory correlation between mortality and the structure of the health care system. 23 The systematic introduction of this aspect in the planning process, as it is projected in Quebec, would have at least three effects:…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is quite possible that the work of the health care system is more closely related to disability than to mortality, as evidenced by the difficulty experienced in establishing a satisfactory correlation between mortality and the structure of the health care system. 23 The systematic introduction of this aspect in the planning process, as it is projected in Quebec, would have at least three effects:…”
Section: Resultsmentioning
confidence: 99%
“…Usually, this production function approach employs conventional regression analysis: for example, in an early cross-sectional study of 18 developed countries, Cochrane et al (1978) used regression analysis to examine the statistical relationship between mortality rates and GNP and consumption of inputs such as health care provision. They found that the indicators of health care inputs were generally not associated with outcomes in the form of mortality rates.…”
Section: Previous Studiesmentioning
confidence: 99%
“…All three inputs had small marginal effects in the case of the United States, whereas literacy and potable water showed significant effects in the less developed countries of the group. Cochrane, St. Leger and Moore (1978) based their analysis on a cross-section of 18 developed countries as of 1970. In their correlation analysis, a greater number of physicians goes along with higher rather than lower mortality (with no attempt to control for reverse causation).…”
Section: The Production Of Healthmentioning
confidence: 99%